Human Facts, Collective Subjects and Author's Worldview in Pendekar Cengeng Silat Story by Kho Ping Hoo - Sidik, Miftahul; Liliani, Else (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research explains the relations and implications of Kho Ping Hoo's discrimination experiences as a Peranakan Tionghoa group to the emergence of the Pendekar Cengeng silat story . Data were collected using reading and note-taking techniques. Data were analyzed using Lucien Goldmann's genetic structuralism theory which focuses on human facts, collective subjects, and the author's worldview. The research results show that human facts include various activities carried out by warrior figures in an effort to oppose the oppression of the colonial government. The collective subject shows a group of warriors who work together and are united in one group to carry out the warrior's mission collectively. The author's worldview are about politics, religiosity and life philosophy.